Is Conservative Working Capital Management the Key to Sustainable Business Growth? - Naning Margasari; Nindya Nuriswati Laily; Lina Nur Hidayati; Heny Kurnianingsih (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: This study examines the nonlinear relationship between working capital management and sustainable growth among non-financial firms listed in the Indonesian LQ45 Index during 2015 to 2025. Research Design & Methods: Using quadratic panel regression analysis on 385 firm-year observations, this study investigates whether aggressive and conservative working capital strategies influence sustainable growth differently at various working capital levels. Working capital management is measured using Days Inventory Outstanding (DIO), Days Sales Outstanding (DSO), Days Payables Outstanding (DPO), and Working Capital Intensity (WCI), while sustainable growth is measured using Higgins’ Sustainable Growth Rate model. Findings: The results show that DIO, DSO, and DPO have an inverted U-shaped relationship with sustainable growth, suggesting that moderately conservative working capital policies initially improve sustainable growth, but excessively conservative policies eventually reduce efficiency and growth sustainability. The effect of WCI on sustainable growth was found to be insignificant. Implications & Recommendations: These findings support Trade-Off Theory, which emphasizes balancing liquidity protection and operational efficiency. The findings suggest that firms should avoid excessively aggressive or excessively conservative working capital strategies. Instead, firms need to identify optimal working capital levels that balance liquidity protection and operational efficiency to support sustainable long-term growth. Contribution & Value Added: This study contributes to the literature by extending working capital management research toward sustainable growth using a nonlinear framework in an emerging market context.